Purwarupa Pembersih Pipa Otomatis (Automatic Tube Remover) pada Heat Exchanger Menggunakan Teknik Pengolahan Citra - Hermawati Sholeh; Bhakti Yudho Suprapto; Andi Pranata; Firmansyah Firmansyah (Jurnal Rekayasa Elektrika, 2015)
In the industry era, especially the oil processing industry, the heat exchanger is needed to regulate temperature and produce oil products such as petroleum, kerosene and diesel fuel. In the operation, the heat exchanger requires maintenance, especially when the minor unit is shut down or stop and routine reparation. Maintenance is done by replacing the tubesheet that commonly referred to as bundle retube where there are pipe fritter to be cleaned, which are cutted at the time of maintenance. This maintenance is typically done in manual approach, which is not efficient in terms of time. For a more efficient maintanence, this paper proposes a prototype design to discard these pipes fritter by utilizing image processing method for detecting the edge of the circle and the position of the pipe fritter. Based on the experiments, it has been obtained that the test circle radius that can be captured is at 4 to 10 pixels. The longest time for positioning was 2.41 minutes and the whole process of disposal of this pipeline reaches 47.92 %.